2022
DOI: 10.1186/s13018-022-02972-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of preoperative deep venous thrombosis following pelvic and acetabular fractures: a retrospective case–control study

Abstract: The objective of this study was to investigate the prevalence of preoperative deep venous thrombosis (DVT) in the pelvic cavity and lower extremities following pelvic and acetabular fractures and to identify the risk factors of the occurrence of DVT. Duplex ultrasound (DUS) screening and blood tests were conducted in patients admitted from June 2012 to December 2020 for surgical treatment of pelvic and acetabular fractures. Univariate analyses were performed on data of demographics, comorbidities, time from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…24 Most patients with DVT have no obvious symptoms, and if there is no in-time therapy, pulmonary embolism will form, which has a high fatality rate. 25 Therefore, it is necessary to investigate biomarkers that are correlated to DVT. The endothelium plays an important role in maintaining normal blood flow and preventing thrombosis formation.…”
Section: Discussionmentioning
confidence: 99%
“…24 Most patients with DVT have no obvious symptoms, and if there is no in-time therapy, pulmonary embolism will form, which has a high fatality rate. 25 Therefore, it is necessary to investigate biomarkers that are correlated to DVT. The endothelium plays an important role in maintaining normal blood flow and preventing thrombosis formation.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, these fractures can prove to be fatal, particularly when combined with preoperative deep venous thrombosis (DVT). It is reported that the incidence of a thromboembolic event is 13.5-33.7% and even 57.6% in severe traumatic cases [ 3 6 ]. To monitor and identify DVT, colour Doppler ultrasound is applied frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the nomogram model is a novel and convenient tool and has been widely used to predict outcomes and complications in various diseases [ 7 11 ]. To date, several investigations have evaluated the risk factors of venous thromboembolism [ 3 5 , 12 , 13 ]. However, none of them developed a nomogram.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to hip fractures, pelvic fractures are associated with high hospitalization rates, significant morbidity, and mortality and may lead to serious individual and socioeconomic burdens. Most patients with pelvic fractures die not from the pelvic fracture itself, but from the associated injury and decline in health status [ 2 ]. Pelvic fractures are underestimated osteoporotic or fragility fractures [ 3 ].…”
Section: Introductionmentioning
confidence: 99%